Hoja de ruta, ¿hacia dónde? - Said, Edward (Revista de Estudios Árabes, 2014)
Professor Edward Said concludes that the Road Map demands are overwhelmingly heavy on the Palestinian side (stop armed resistance against the occupying forces, government reforms, disarm the militias, etc.); demands on Israel are insignificant (dismantle some illegal settlements and somehow make Palestinian daily lives easier). No mention is made of human rights violations, nor of the Separation Wall and its damaging consequences for the Palestinians. No timetables are fixed either. His analysis of Abu Mazen portrays a bureaucratic man who works behind the scene, close to the West. He was one of the architects of the Oslo accords, which were ill-prepared and brought about catastrophic results for the Palestinians. A new and fast growing independent movement, the Palestinian Initiative, whose Director is Dr. Mustapha Bargouthi, is gaining ground among the masses. The movement is known for contacting any government that wishes to collaborate with the Palestinian people. It has a solid reputation of honesty and efficiency, is democratic in its conception and advocates for a state on all Palestine at once.